Sodium and potassium levels in colostrum - Yurdakök, Murat; Oran, Olcay; Tekinalp, Gülsevin (The Turkish Journal of Pediatrics, 1991)
The sodium and potassium concentrations of serum, urine and breast milk from 40 healthy, lactating mothers aged 18 to 35 years were measured. Nineteen women were primiparous and 26 were delivered prematurely for various reasons. No correlation was found between colostrum and urine sodium and potassium levels, and colostrum and serum potassium levels, however, there was a correlation found between colostrum and serum sodium levels (r: 0.311, p
Keywords: colostrum; sodium; potassium